Potential of okra (Abelmoschus esculentus L.) extract to reduce blood glucose and malondialdehyde (MDA) liver in streptozotocin-induced diabetic rats - Anjani, Putri Puncak; Damayanthi, Evy; Rimbawan, Rimbawan; Handharyani, Ekowati (Jurnal Gizi dan Pangan, 2018)
The study aimed to analyze the potential of okra to reduction blood glucose and MDA liver in streptozotocin (STZ)-induced diabetic rats. Design experiment used in this study was pre and post test controlled group design. The first step of this study was analyzed bioactive compound of okra extract. The next step was administired orally of okra extract to control and diabetic rats induced by streptozotocin 50 mg/kgBW for 14 days. Sprague dawley rats were divided into six groups: normal control (N), diabetic control (DM), diabetic treated with green okra extract (GOE) with the dosage of 5 mg/kgBW quercetin and 10 mg/kgBW quercetin, diabetes treated with purple okra extract (POE) with the dosage of 5 mg/kgBW quercetin and 10 mg/kgBW quercetin. Blood glucose were measured each five days and malondialdehyde (MDA) liver in rats were measured in the end of intervention. The following results show that phenolic and quercetin of purple okra extract were higher (3.60%; 0.45 mg/g) than green okra extract (3.58%; 0.27 mg/g). Administration of GOE I, GOE II, POE I and POE II in diabetic rats showed significant (P<0.05) reduction in blood glucose level (115.25 mg/dl; 86 mg/dl; 180.75 mg/dl; 91 mg/dl) and improve level of MDA. These results suggest that intervention of okra extract based on quercetin compound show an antihyperglicemic potential and improve MDA level.